PREPARATION D’ADN GENOMIQUE DE STAPHYLOCOCCUS AUREUS PAR LYSE AVEC LE CARVACROL - Louasté Bouchra; Boudine Latifa; Eloutassi Noureddine (European Scientific Journal, ESJ, 2014)
This work is a development of a genomic DNA extraction methodfrom Staphylococcus aureus. This procedure uses just carvacrol in the step ofcell lysis. This is a simple, fast and economical, in addition, the extractedDNA was in good quantity and quality and can be used in variousapplications of molecular biology.